Economic Time - John F. Henry; L. Randall Wray (Levy Economics Institute of Bard College, 1998)
This paper argues that economists require a particular concept of time to develop theory with greater explanatory power in describing and analyzing the sort of economy in which we are primarily interested–the monetary economy usually termed capitalism. Economists of various persuasions have recognized the importance of a concept of time, but we argue that a very specific concept is required. We propose a concept of time that is consistent with the perception and experience of time in a monetary or capitalist economy. This concept of time is determined by the debt cycle, and the length of this cycle is determined by the interest rate. Thus, while our proposed time measure is certainly historical and sequential in nature (months, years), it is not simply clock time: the length of economic time is fluid and is regulated by the interest rate, a variable of significance in dictating a host of socially important effects.
Keywords: 330